Klarifikasi Makna Nilai Personal dalam Pembentukan Moral Pendidikan - Faridatul Munawaroh; Nova Adi Kurniawan (STAI Auliaurrasyidin Tembilahan, 2020)
This article clarifies the meaning of personal values on creating moral education. Meaning clarification of values is a special identity to mind, feeling, and attitudes. Values clarification is in coherence with normal physical development. Education and assessment should touch the stages of the development. The stages of mind development consist of theological, metaphysical, positive, and existence. Existence consist of eclectic, etic, and religious. Meanwhile, fostering moral should develop moral knowing, moral feeling, and moral action.